ESL writing apprehension: Level, causes and strategies to overcome It - Nurul Nadia, Muhammad; Siti Norzaimalina, Abd Majid; Rosnani, Ismail (Asian Scholars Network, 2025)
Writing, whether in the first or second language, is often regarded as a challenging process. On top of that, the feelings of fear, anxiety and worry would make the learning process more difficult as these negative feelings will affect the learners’ focus. Hence, this study aims to explore Diploma Engineering students’ level and causes of writing apprehension, as well as their preferred learning strategies to reduce writing apprehension. A total of 125 Diploma students from 4 engineering faculties at a local public Malaysian technical university were involved in this study and the data was collected through an online questionnaire that consists of 22 items adopted from the Second Language Writing Anxiety Inventory (SLWAI), 10 items on the Causes of Writing Anxiety Inventory (CWAI), and another 10 items on strategies to reduce writing apprehension. The findings revealed that 44% of the students experienced a high level of writing apprehension, while 36.8% experienced moderate level of writing apprehension, and only 19.2% were reported to have low level of writing apprehension. In addition, it was discovered that fear of the teacher’s negative comments, linguistic difficulties and pressure for perfect work are the top 3 factors contributing to the students’ writing anxiety. As for the strategies to reduce writing apprehension, it was revealed that interactive pedagogy, scaffolding students’ writing skills and clear instructions were crucial in helping the students to overcome their fear of writing. The findings of this study may alert English language instructors of the negative effects of writing anxiety, and the need for differential instructional methods and materials to support highly anxious writers to gradually improve their writing skill performance.